On the treatment of degeneration of the macula and posterior pole (Ukrainian Journal of Ophthalmology, 2025)
Background: The field of degeneration of the macula and posterior pole (DMPP) is of outstanding medical and social significance as the disease is of high prevalence and leads to loss of general working capacity.Purpose: To determine the efficacy of conservative treatment with endonasal iontophoresis of Omk2, and the degree of stabilization of visual functions after this treatment in patients with DMPP.Materials and Methods: Thirty-two patients (45 eyes; age, 51 to 75 years) with DMPP were examined and received treatment with endonasal iontophoresis of Omk2. The eye examination included visual acuity, retinal light sensitivity, threshold assessment with macula tester, perimetry and ophthalmoscopy, and was performed before and after treatment.Results: In all patients with DMPP, iontophoresis of Omk2 contributed to apparent improvement in functional activity of the retina, which was achieved due to antioxidative, neurotropic, anti-edema and anti-angiogenetic properties of the drug. In particular, mean uncorrected visual acuity (UCVA) in patients of group 1 improved by 25%, from 0.6 to 0.85, and UCVA in 49% of patients of group 2 improved by 0.01-0.02, which improved the level of social rehabilitation of these patients. In patients with DMPP, the treatment with iontophoresis of Omk2 resulted in improvements in the functional activity of the retinal photopic system and foveal afferent system (as assessed by the Haidinger’s brushes test), and retinal blood flow in the posterior pole (as assessed by the blue field technique) by 33-43%, 14%, and 40%, respectively. This demonstrates that the treatment strategy has the beneficial impact on the function of the visual system, and iontophoresis of Omk2 is a pathogenetically reasonable approach to the management of DMPP.Conclusion: Iontophoresis of Omk2 was found to be beneficial for the function of the visual system, and a pathogenetically reasonable approach to the management of DMPP.
Keywords: degeneration of the macula and posterior pole; iontophoresis of Omk2